Replaced: Andalucía, national belonging, and Jewishness in Lorca's Los títeres de Cachiporra. Issue 4 (2nd October 2021) - Cohn, Adam
Abstract: Federico García Lorca's fascination with the cristobicas, a traditional Andalusian puppet show, led him to write and stage a number of these plays from early on in his career. Scholars of Lorca's guignol often note that through the revitalization of this endangered art form, the young playwright sought to bring innovation to Spain's theater. As a result, the actual contents of these plays have received little attention, and are generally viewed as using stock characters and conventional plots. The present article argues that Los títeres de Cachiporra (1922) stages a modern version of the Spanish nation as lived in Andalucía through a farcical take on the el viejo y la niña marriage plot. Specifically, I illustrate how Rosita's three suitors have different relationships with regnant power structures and display various degrees of rootedness to the Andalusian town where the action unfolds. Particular attention is paid to Rosita's former lover, Currito, who returns after abandoning both her and the town five years earlier. I demonstrate that the anti-Semitic insults directed at Currito reveal a deeper anxiety over who should be included in the modern Spanish nation. Contextualizing these comments among broader trends in European anti-Semitism and Spanish philo-Sephardism in the early twentieth century, I argue that Jewishness is a productive analytic for understanding Currito's function in the play. A superseded Jewishness, in a final analysis, becomes the counterpoint against which Spanishness is measured.